G185(P) Innovative e-learning: a uk initiative to advance undergraduate paediatric medical education. (27th April 2015) - Vernon, S; Russell, S; Nesbitt, A; Morrissey, B
Abstract : Aim: In the USA, on-line interactive clinical cases are increasingly being used to support and deliver the undergraduate paediatric curriculum. The use of e-learning in undergraduate paediatrics in the UK is limited by a lack of case complexity and instantaneous feedback to learners. We aimed to develop and evaluate an interactive and accessible paediatric case scenario for undergraduates. Methods: Clinical students at a UK medical school were surveyed using a Google Docs questionnaire. Their feedback was used to develop an innovative powerpoint-based e-learning format. Our two simulated cases, on neonatal jaundice and neonatal sepsis, aimed to replicate real-life clinical practice. By presenting learners with several different clinical scenarios simultaneously we hoped to further their competency in clinical decision making, patient prioritisation, prescribing skills and emergency care. Hyperlinks were utilised to allow for instantaneous feedback, enable easy access to external resources (e.g. NICE) and simulate consequences for learners' decisions. Upon completion students were asked to fill out a second feedback survey. Numerical data was analysed in Stata 12.1 using the Wilcoxon signed rank test, and free-text responses evaluated thematically. Results: 59 students responded to the initial survey. 85% stated that they used case studies primarily to consolidate knowledge and effectively test understanding. 83% wanted instant and easy access to more case studies. Learners expressed frustration that current online cases focussed on barn door presentations that did not identify gaps in their knowledge. There was concern that current cases were unrealistic and lacked integration of problem solving skills. Learners were also dissatisfied at the time lag between answering white space questions and receiving feedback. Students' self-rated knowledge increased from 2.51/4 (95% Cl 2.27–2.76) to 3.6/4 (95% Cl 3.41–3.79), after completing the case study; p < 0.0001. Students valued having to 'prioritise multiple patients' and 'make decisions about the child's care'. They praised 'the ability to interact with the powerpoint', and the provision of concise, relevant and instantaneous feedback. Conclusion: We have designed a novel, effective and inexpensive case study format that supports learning in paediatrics. Our e-learning method mirrors the complexities and challenges of real-life clinical practice and enables development of clinical decision making.